Gejala Depresi pada Warga Binaan Perempuan di Lembaga Pemasyarakatan - Ilma Widiya Sari; Mateus Sakundarno Adi; Megah Andriany (Holistic Nursing and Health Science, 2019)
Introduction: Stressors of prison life can cause women prisoners to become depressed. The differences in symptoms of depression among women prisoners and the general population may occur due to the characteristics of prisoners and the nature of the prison environment. Symptoms of depression among women prisoners are important to know to prevent the negative effects of depression. This study aimed to describe the symptoms of depression among women prisoners.Methods: A quantitative descriptive study involving 66 women prisoners was designed. Sampling technique using purposive sampling. Self-report surveys using Beck Depression Inventory II were conducted to collect data related to showed the symptoms of depression. Univariate analysis was used to describe the symptoms of depression in frequency distribution and percentage.Results: Symptoms of depression can be divided into three domains include cognitive, affective and somatic. This study showed that the symptoms of depression most commonly experienced by women prisoners are sadness (97%), agitation (85%) and sleep disorders (70%).Suggestion: The findings suggest that early symptoms of depression identification can help professional to minimize the negative effects of depression. Further research is needed to overcome depression among women prisoners.